The secrets of bones [large type] - Logan, Kylie (Thorndike Press large print mystery series., 2020)
"Assembly Day at St. Catherine's dawns bright and cloudless as professional woman gather from all around Ohio to talk to the schoolgirls about their careers ranging from medicine, to NASA, to yoga. Jazz Ramsey has also signed up to give the girls a taste of her lifelong passion: cadaver dog training. Her adorable new puppy Wally hasn't been certified yet, so she borrows the fully-trained Gus from a friend and hides a few bones in the unused fourth floor of the school for him to find. The girls are impressed when Gus easily finds the first bone, but then Gus heads confidently to a part of the floor where Jazz is sure no bones are hidden--at least not any that she's put there. But Gus is a professional, and sure enough, behind a door that no one has opened in ages, is a human skeleton. Jazz recognizes the necklace the skeleton is wearing, and that it belonged to Bernadette Quinn, an ex-teacher at the school who'd quit her job abruptly one Christmas break. But now it seems Bernadette never left the school at all, and her hiding place makes it clear: this was murder. Bernadette in life had been a difficult personality, and so there are a plethora of suspects inside the school and out of it. As Jazz gets closer to the truth she can't help but wonder if someone might be dogging her footsteps.."--